Digital natives and mobile payment: Do individual affective responses influence technology adoption and recommendation intention? - Sigit Pamungkas; Triana Linggasari (Jurnal Akuntansi dan Auditing Indonesia, 2021)
Technology advancement has transformed the recent trend of payment method from a traditional cash system to the use of electronic device connected to wireless network, known as mobile payment system. This study reviews the research model conducted by Verkijika (2020) which aimed to measure the effect of individual affective responses on the acceptance of mobile payment system by combining two theories: Social Cognitive Theory and Regret Theory. In particular, this research was conducted to observe the effects of affective responses on the behavior of digital native users. The structural model was applied to test the hypotheses using the SmartPLS 3.0 application. The data obtained through questionnaires collected from 301 respondents in Indonesia. The results of this study presented a variety of findings that were different from the comparative study. The findings indicate that there is no single affective factor that dominates the influence (of what?) on the users’ intentions to adopt and to recommend the use of mobile payment technology.